Audit Quality Determinants with Audit Report Lag as a Moderator on State-Owned Enterprises in Indonesia - Rohmah, Fian Tri; Pramono, Maylia; Mussanadah, Atik Ul (JAFFA, 2024)
This research examines the moderating role of audit report lag (ARL) with the association between foundational audit elements (audit firm rotation, auditor switching, audit fees, and auditor gender diversity) and audit quality. By focusing on State-Owned Enterprises (SOEs) listed under the BUMN20 Index, it employs descriptive and inferential statistical analyses through panel data regression and Moderated Regression Analysis (MRA). The findings reveal that all non-moderated associations do not considerably influence audit quality. Inference from the moderation role, it is found that ARL weakens the correlation of audit fees and auditor gender diversity on audit quality. Shortly, it indicates the critical importance of maintaining output quality and timeliness in auditing.